PENGARUH KEAHLIAN KOMITE AUDIT DAN JUMLAH RAPAT KOMITE AUDIT TERHADAP MANAJEMEN LABA DENGAN MODERASI AUDITOR EKSTERNAL - Hamzah Hamzah; Dul Mu'id (Diponegoro Journal of Accounting, 2018)
Audit committee and External auditor have a very important role to oversee the financial reporting process and monitor the propensity of a company managers to manipulate earnings. Monitoring mechanism is a key factor to reduce conflicts of interest and any opportunistic behavior from the manager. This study aims to examine the effect of audit committee expertise and the amount of audit committee meetings on earnings management with External auditor as a moderating variable in the manufacture companies in Indonesia.The type of data used in this study is secondary data and the total number of samples in this study were 104 data companies that constantly registered in LQ-45 index and listed in Indonesia Stock Exchange from 2014-2017. The sampling method in this research uses purposive sampling technique for the company that has been registered in LQ-45 index and listed in Indonesia Stock Exchange which published annual report in 2014-2017. Variable earnings management, audit committee expertise, the amount of audit committee meetings, and External auditor analyzed by multiple linear regression model. The result of the study indicate that audit committee expertise significantly negative impact on earnings management and the amount of audit committee meetings not significantly impact on earnings management. Audit committee expertise moderated by External auditor positive effect and significant on earnings management. However, the amount of audit committee meetings moderated by External auditor not significant on earnings management.